Independent association of Lp(a) with platelet reactivity in subjects without statins or antiplatelet agents - Liu, Huixing; Fu, Di; Luo, Yonghong; Peng, Daoquan (Scientific reports, 2022)
The physiological effect of Lp(a) on platelet activity is unclear. Previous studies explored the relationship between Lp(a) and platelet aggregation in patients taking statins and antiplatelet agents, but few was conducted in individuals without the bias of those drugs that either influence Lp(a) or platelet activity. The aim of this study was to assess the relationship between Lp(a) levels and platelet aggregation in subjects not taking statins or antiplatelet drugs. A hospital-based cross-sectional study was conducted to investigate the independent contribution of Lp(a) to platelet activity by controlling the effects of potential confounding factors including lipoprotein-associated phospholipase A2 [Lp-PLA2]. Blood samples were collected from 92 subjects without statins or antiplatelet agents from the Second Xiangya Hospital. The univariate correlation analysis showed a significant correlation between AA-induced average aggregation rate [AAR] and ApoB (r = 0.324, P = 0.002), ApoA1 (r = 0.252, P = 0.015), Lp(a) (r = 0.370, P < 0.001), Lp-PLA2 (r = 0.233, P = 0.025) and platelet counts [PLT] (r = 0.389, P < 0.001). Multivariate regression analysis suggested that Lp(a) contributed independently to AA-induced average aggregation rate (β = 0.023, P = 0.027) after controlling for the effects of ApoB, Lp-PLA2 and platelet counts. Lp(a) is positively associated with platelet aggregation independent of Lp-PLA2, which may partly account for the atherothrombotic effect of Lp(a).